Avaliação da variabilidade genética e agrupamento de acessos e cultivares de Brachiaria por marcadores de RAPD. - Ambiel, Ana Claudia (2007)
The aim of this work was the determination of intra and intergenetic similarity between three Brachiaria species among germplasm accesses and commercial materials throughout RAPD markers. Seeds were used as DNA source. 10 decamers primers were selected between 120 primers assayed and 107 polymorphic bands were used to perform the molecular variance analysis (AMOVA), Jaccard similarity and species fixation index. 24.4% of the total variability was contained between species and 75.6% inside the species, with a species fixation index (FST) of 0.24. The tree showed that two major branches were formed, one with the three outgroup species and other with the species, this one split in three minor branches one with all B. ruziziensis samples; other with all B. decumbens accessions and three of B. brizantha and the last with two B. brizantha accesses, all commercial cultivars and B. decumbens cv. Basilisk . It was possible to group, throughout RAPD, Brachiaria accesses and cultivars. The genetic variability index between species was considered low and somehow low when faced with autogamous species. B.brizantha showed the highest genetic variability and the lowest FST what means that there is a higher genetic flux intra specific than the others.